Crop-livestock systems research in the Andean region: ecoregional approach, methods and procedures - León Velarde, C.U.; Quiróz, R. (International Livestock Research Institute, 1999)
Increased population, low agricultural productivity, pressure on land and overexploitation of natural resources, are current problems in the Andean ecoregion. Knowledge of the region is vast, but results from site-specific research have seldom been integrated. A holistic ecoregional research approach is required to solve the problems and contribute to regional development. To this end, the appropriate definition of the term ecoregion and the proper use of methods and procedures to generate and adapt technology are necessary for sustainable development. This paper aims to present the integration and management of knowledge in a holistic way for the effective application of systems analysis research in an ecoregional context.